2022
DOI: 10.1097/md.0000000000030380
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of systemic immune-inflammation index in patients with bladder cancer: A systematic review and meta-analysis

Abstract: Background: Systemic Immune-inflammation Index (SII) has been shown to correlate with the prognosis of numerous malignancies, but researchers have not yet reached an agreed conclusion on bladder cancer. To fill the blank, we conducted a meta-analysis to assess the prognostic role of SII in the prognosis of bladder cancer.Methods: After analyzing relevant literature published in PubMed, China National Knowledge Infrastructure, EMBASE, Cochrane Library, and Web Science up to April 30, 2022, we collected 83 artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In the metaanalysis involving eight studies carried out by Zhou et al, the higher SII remarkably predicted poor OS and extensive-stage among patients with small cell lung cancer (SCLC) (30). As shown by Cao et al in a meta-analysis of 11 studies, an increased SII before treatment remarkably predicted dismal OS, CSS, PFS, and recurrence-free survival (RFS) inpatients with bladder cancer (50).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the metaanalysis involving eight studies carried out by Zhou et al, the higher SII remarkably predicted poor OS and extensive-stage among patients with small cell lung cancer (SCLC) (30). As shown by Cao et al in a meta-analysis of 11 studies, an increased SII before treatment remarkably predicted dismal OS, CSS, PFS, and recurrence-free survival (RFS) inpatients with bladder cancer (50).…”
Section: Discussionmentioning
confidence: 96%
“…As shown by Cao et al. in a meta-analysis of 11 studies, an increased SII before treatment remarkably predicted dismal OS, CSS, PFS, and recurrence-free survival (RFS) inpatients with bladder cancer ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…20 In the study by Cao et al meta-analysis revealed that high pretreatment SII levels in bladder cancer patients were significantly associated with worse overall survival, cancer-specific survival, and relapse-free survival. 21 In a study with Bechet’s patients, the SII value was shown to be worse. It was higher in active Bechet’s patients and the cut-off value was >552.12 × 10 3 /mm 3 when deciding on treatment.…”
Section: Discussionmentioning
confidence: 99%
“…SII can be easily obtained preoperatively. It has been reported to be predictive of OS and disease-free survival in different types of cancer [ 33 , 34 ]. There is at least one study in advanced pancreatic cancer, but several others with resection of other cancers [ 35 - 37 ].…”
Section: Discussionmentioning
confidence: 99%